Pyrogallol Red Oxidation Induced by Superoxide Radicals: Application to Evaluate Redox Cycling of Nitro Compounds - Lissi-Gervaso, E (2011)
The bleaching of the pyrogallol red (PGR) dye mediated by superoxide anion radicals (O2-) generated from the xanthine/xanthine oxidase system (X/XO) was studied by UV-visible spectrophotometry. The absorption band (at 540 nm) of PGR quickly decreased in the presence of X/XO, implying an efficient reaction of O2- with PGR. The process was unaffected by catalase (CAT), but completely abolished by superoxide dismutase (SOD). A mechanism of the reaction involving the consumption of one PGR molecule by two O2- to generate one molecule of H 2O 2 is proposed. PGR was used as a probe to estimate the rate of O2- generation in redox cycling reactions of a series of nitro compounds mediated by rat liver microsomes. The consumption of PGR induced by the redox cycling of nitrofurantoin was totally eliminated by the addition of SOD but unaffected by CAT. The initial rate of consumption of PGR mediated by the redox cycling of others nitro derivatives follows the order: furazolidindione>nitrofurantoin>nifurtimox>benznidazole> chloramphenicol. We concluded that PGR can be used as a probe to estimate the release of O2- from enzymatic systems or from the redox cycling of nitro compounds. © 2011 Elsevier Inc. All rights reserved.